Improving the secretory capacity of CHO producer cells: The effect of controlled Blimp1 expression, a master transcription factor for plasma cells - Kim, Su Hyun; Baek, Minhye; Park, Sungje; Shin, Seunghyeon; Lee, Jae Seong; Lee, Gyun Min (Metabolic Engineering, 2022)
With the advent of novel therapeutic proteins with complex structures, cellular bottlenecks in secretory pathways have hampered the high-yield production of difficult-to-express (DTE) proteins in CHO cells. To mitigate their limited secretory capacity, recombinant CHO (rCHO) cells were engineered to express Blimp1, a master regulator orchestrating B cell differentiation into professional secretory plasma cells, using the streamlined CRISPR/Cas9-based recombinase-mediated cassette exchange landing pad platform. The expression of Blimp1α or Blimp1β in rCHO cells producing DTE recombinant human bone morphogenetic protein-4 (rhBMP-4) increased specific rhBMP-4 productivity (qrhBMP-4). However, since Blimp1α expression suppressed cell growth more significantly than Blimp1β expression, only Blimp1β expression enhanced rhBMP-4 yield. In serum-free suspension culture, Blimp1β expression significantly increased the rhBMP-4 concentration (>3-fold) and qrhBMP-4 (>4-fold) without significant increase in hBMP-4 transcript levels. In addition, Blimp1β expression facilitated mature rhBMP-4 secretion by active proteolytic cleavage in the secretory pathway. Transcriptomic profiling (RNA-seq) revealed global changes in gene expression patterns that promote protein processing in secretory organelles. In-depth integrative analysis of the current RNA-seq data, public epigenome/RNA-seq data, and in silico analysis identified 45 potential key regulators of Blimp1 that are consistently up- or down-regulated in Blimp1β expressing rCHO cells and plasma cells. Blimp1β expression also enhanced the production of easy-to-express monoclonal antibodies (mAbs) and modulated the expression of key regulators in rCHO cells producing mAb. Taken together, the results show that controlled expression of Blimp1β improves the production capacity of rCHO cells by regulating secretory machinery and suggest new opportunities for engineering promising targets that are resting in CHO cells.
Keywords: Blimp1; Bone morphogenetic protein-4; Chinese Hamster ovary cells; CHO cell; Difficult-to-express protein; Human bone morphogenetic protein; Plasma cells; Secretory capacity; Secretory pathways; Targeted integration; Animals; CHO Cells; Cricetinae; Cricetulus; Humans; Plasma Cells; Recombinant Proteins; Transcription Factors; Blimp1; Cell engineering; Chinese hamster ovary (CHO) cells; Difficult-to-express proteins; Targeted integration